“Nós que mudamos, eles não”: a importância do suporte familiar, da idade e do gênero na análise do desenvolvimento da identidade sexual e da saúde mental de lésbicas, gays e bissexuais em Minas Gerais - Samuel Araujo Gomes da Silva (2021)
This dissertation aims to discuss the associations of age, gender, and family support on the development of sexual identity (DSI) and mental health (MH) of lesbians, gays, and bisexuals (LGB) in Minas Gerais. Therefore, we used the mixed method approach through the application of an online survey with 754 LGB residents in the state in 2019. Out of this first sample, 33 individuals also participated in semi-structured interviews. The procedure for selecting respondents for the survey was based on the Respondent Driven Sampling (RDS) technique, as the information on the size and composition of the LGB population in Brazil is not available. The application of the online questionnaire resulted in the construction of an unprecedented database with information on sexual minorities in Minas Gerais, which allowed us to understand the relationship between the development of sexual identity and mental health in this population (specific aim 1). The survey evaluation was based on topological metrics of the networks formed by the respondents' indication chains (connectivity, average path, average degree, and assortativity coefficient) of the networks formed by the respondents' indication chains. We used descriptive, bivariate, multivariate analyzes and the delimitation of multidimensional profiles using the Grade of Membership (GoM) method to investigate the gender and age differentials in DSI and MH results (specific aim 2). Finally, the semi-structured interviews with the 33 LGB individuals were analyzed by combining content analysis techniques and thematic networks. This stage allowed deepening the analysis of the quantitative results and verifying whether institutional changes in favor of sexual and gender diversity are reflected in changes in family support in the DSI process among LGB in the state (specific objective 3). The results suggest that women had DSI milestones at older ages compared to men, but with a shorter interval between recognizing and communicating their sexuality. They also had the worst mental health outcomes, especially among the younger ones. Furthermore, it was possible to identify that despite institutional advances towards sexual and gender diversity in society in general, little has changed within the household of origin concerning the acceptance and care of LGB children. Therefore, the role of family support and the gap between equality in the family and individual-oriented institutions are fundamental elements in the analysis of the mental health of sexual minorities, as well as in public policies and data collection strategies about this population.